Influência da adoção do CPC 47 na gestão do capital de giro e resultado econômico das empresas brasileiras listadas - Bello, Marina de Morais (2025)
Accounting has undergone transformations with the adoption of CPC 47 – Revenue from Contracts with Customers, which standardized revenue recognition across all economic sectors, replacing previous fragmented regulations (Dias & Costa, 2024). This research investigates the effects of the adoption of CPC 47 on working capital management and the economic performance of Brazilian companies listed on [B]³, analyzing periods before and after the mandatory implementation of the standard. Quantitative analysis techniques were employed, including robust linear regressions, quantile regressions, and non-parametric tests, to assess statistical differences between periods and sectors with higher and lower exposure to the standard. The sample comprises 1,610 observations of companies listed on [B]³ between 2010 and 2023, excluding financial institutions. The variables of interest include the Cash Conversion Cycle (CCC) and Return on Assets (ROA), along with control variables such as company size, COVID, financial leverage, and corporate life cycle stage. The OLS linear regression results indicate that the adoption of CPC 47 did not significantly impact working capital management and economic performance in a generalized manner. However, sector-based analysis, through additional hypotheses, revealed that companies more exposed to the standard, such as those in Construction and Industrial Goods, experienced greater changes in working capital management, while Industrial Goods, Healthcare, and Technology sectors showed negative impacts on economic performance, confirming sectoral variations. The quantile regression, used as a robustness test, revealed that the impacts of CPC 47 were not homogeneous across the distribution of financial variables. Companies with longer cash conversion cycles adjusted their strategies to reduce CCC after the adoption of the standard, while companies at the extremes of the ROA distribution (less profitable and highly profitable firms) were the most negatively affected. The findings contribute to the literature by demonstrating that accounting standardization can have differentiated effects across economic sectors. From a practical perspective, the study provides valuable insights for regulators, managers, and investors regarding the financial impacts of adopting new accounting standards and their implications for the predictability of corporate results.